2017
DOI: 10.1002/pbc.26743
|View full text |Cite
|
Sign up to set email alerts
|

Household material hardship in families of children post‐chemotherapy

Abstract: Poverty is an important patient-reported outcome of therapy and a potential predictor of outcome disparities in pediatric cancer. We previously identified that nearly 30% of pediatric cancer families experience household material hardship (HMH), a concrete measure of poverty including food, energy, or housing insecurity, during the first 6 months of chemotherapy. We conducted a follow-up survey in a subcohort of these families at least 1 year off-therapy and found that 32% reported HMH in early survivorship. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 16 publications
0
57
2
2
Order By: Relevance
“…We identified 3359 articles through literature searches and included 35 articles, reporting on 29 individual studies (Figure ). Thirteen (37%) studies were conducted in Europe, 16 (46%) in North America/Australia, and six (17%) in Asia/Africa (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 3359 articles through literature searches and included 35 articles, reporting on 29 individual studies (Figure ). Thirteen (37%) studies were conducted in Europe, 16 (46%) in North America/Australia, and six (17%) in Asia/Africa (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies on income reported substantial income loss after the child's diagnosis . The proportion of parents reporting income loss and the extent of these losses varied largely.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a cross-sectional survey, we found that the large majority of PCPs had provided acute medical care to on-therapy patients with childhood cancer (70% of PCPs) and health maintenance care to childhood cancer survivors (91% of PCPs) in their practices within the past year. Additional barriers to accessing specialty care for minor illnesses during cancer treatment or health maintenance during survivorship may include household material hardship 36,37 and the absence of infrastructure such as mass transit in rural areas. In addition, these findings also likely point to the complexities of patient access to specialized pediatric oncology care in states such as Alabama that have broad geographic areas that encompass large rural populations.…”
Section: Discussionmentioning
confidence: 99%